Identification and characterization of an anthrol reductase from Talaromyces islandicus (Penicillium islandicum) WF-38-12. Issue 24 (21st November 2019) - Singh, Shailesh Kumar; Mondal, Amit; Saha, Nirmal; Husain, Syed Masood
Abstract : An NADPH-dependent oxidoreductase from Talaromyces islandicus WF-38-12, identified through genome analysis, catalyzes the regio- and enantioselective reduction of substituted anthrols. Abstract : An NADPH-dependent oxidoreductase from Talaromyces islandicus WF-38-12 has been identified through genome analysis. It has been shown to catalyze a regio- and stereoselective reduction of anthrols (formed in situ by the reduction of anthraquinones in the presence of Na2 S2 O4 ) to ( R )-dihydroanthracenones, with high enantiomeric excess (>99%). The implications of results on the biosynthesis of deoxygenated (bis)anthraquinones and modified (bis)anthraquinones are discussed.